2020
DOI: 10.3390/atmos11070690
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpene Chemical Speciation with High Time Resolution Using a FastGC/PTR-MS: Results from the COV3ER Experiment on Quercus ilex

Abstract: Monoterpenes (MTs) represent an important family of biogenic volatile organic compounds (BVOCs) in terms of amount and chemical diversity. This family has been extensively studied using gas chromatography (GC) and proton transfer reaction-mass spectrometry (PTR-MS). Upon recent advances with Fast Gas Chromatography (FastGC), it was also commercialized with proton transfer reaction-time of flight-mass spectrometry (PTR-ToF-MS) instruments. The combination of both techniques showed promising results in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In particular, the DBSS allowed identifying the typical compounds emitted by Q. ilex. Indeed, qualitative MTs identification carried out in our study is consistent with results reported in previous experiments conducted on the same species both in pots and in field conditions [49,50,65,66]. In all sampling points, α-pinene, α-thujene, β-pinene, sabinene and d-limonene were the most abundant compounds emitted by Q. ilex [5,46,48], which represented about 65-80% of the total detected monoterpenes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In particular, the DBSS allowed identifying the typical compounds emitted by Q. ilex. Indeed, qualitative MTs identification carried out in our study is consistent with results reported in previous experiments conducted on the same species both in pots and in field conditions [49,50,65,66]. In all sampling points, α-pinene, α-thujene, β-pinene, sabinene and d-limonene were the most abundant compounds emitted by Q. ilex [5,46,48], which represented about 65-80% of the total detected monoterpenes.…”
Section: Discussionsupporting
confidence: 90%
“…In all three sampling points, the only terpenes identified were monoterpenes and monoterpenoids (MTs), while no sesquiterpenes or other BVOCs were detected. Indeed, the Q. ilex BVOC emission pattern is mainly characterized by monoterpenes [45][46][47][48][49][50]. In the first sampling point, there were no differences in MTs collected using the two sampling techniques (DBSS and static sampling).…”
Section: Bvoc Identification and Qualitative Analysismentioning
confidence: 91%
“…Plant VOCs also affect the food web by serving as cues for herbivores to localize their host plants, or as a food source for microbes in both the rhizosphere and phyllosphere [8][9][10]. Owing to their multiple roles in plant ecology and advances in the real-time detection of trace gases (e.g., [11,12]), the study of VOCs that are emitted by crop plants has received increasing attention in the field of agroecology and crop protection. Provided that the emitted VOCs can be unequivocally identified and quantitatively measured without disturbing the actual physiological status of the plants, the online monitoring of the volatile metabolome represents a valuable non-invasive tool for early stress detection and survey of variation in plant fitness and phenology [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For C. japonica, the emission rates of α-Pinene, β-Pinene, and α-Phellandrene accounted for 61%; for C. obtusa, α-Pinene, β-Pinene, and D-Limonene accounted for 63%; and for P. densiflora, α-Pinene, β-Pinene, and β-Myrcene accounted for 95% of the total monoterpene. Similarly, emissions of α-pinene, sabinene, β-pinene, myrcene, and limonene from Q. ilex L. are strongly affected by light intensity and leaf temperature [75,79,[89][90][91]. Despite knowledge about the light intensity-monoterpene correlation, the effect of light on the emissions from non-woody plant species needs further investigation.…”
Section: Sunlightmentioning
confidence: 99%